PENGARUH UKURAN, PERTUMBUHAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL INTERVENING HARGA SAHAM - Rahayu, Septian Dwi (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This research aims to test and analyze the influence of size, growth and leverage on company value with the intervening variable stock price. The population in this research are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2020-2022. Meanwhile, the sample in this study was 22 companies selected using the purposive sampling method. This research uses a quantitative research type and approach. The data collection method used in this research is secondary data obtained from the Indonesia Stock Exchange website, namely in the form of annual financial reports. The data analysis method used in this research is Descriptive Statistical Analysis, and Inferential Statistical Analysis. Data analysis was carried out using statistics with the SmartPLS version 4.0 tool. Based on the results of data analysis using hypothesis testing, it shows that company size and company growth have a significant effect on share prices, while leverage has no significant effect on share prices. Company size, leverage, and share price have a significant effect on company value, while company growth does not have a significant effect on company value. Company size and company growth have a significant effect on company value through share prices, while leverage does not have a significant effect on company value through share prices.